PROFETICAL LEADERSHIP IN THE PERSPECTIVE OF MUHAMMDAH ABU HAM BIN MUHAMMAD AL GHAZALI (1058 - 1111 AD) - asriyah, masfiyatul (EARR (Educational Administration Research and Review), 2020)
Ethically good leadership must be able to provide accountability to the Creator, the community, educational institutions that are led and always guided by the Holy Qur'an and the Hadith. Abu Ham Muhammdah ibn Muhammad al-Ghazali (1058-1111 AD hereinafter referred to as al-Ghazali) was one of the initiators of the ethics of leadership with the magnum opus of Ihyâ’ Ulûmuddîn. One of al-Ghazali's thoughts is that leadership must refer to the values of nubuwwat (prophecy), namely as an effort to obtain guidance or guidance from Allah SWT. This leadership is rooted in the situational leadership exemplified by the Prophet in the organization that starts from planning, implementation, and evaluation.This research is a library research, which is a researcher looking for data that is directly related to prophetic leadership through the works of Islamic education experts especially Al-Ghazali, both in the form of books, articles or in other forms. Data collection is done by means of documentation (documentary study). The results and findings in the study are the Prophetic leadership in the Al-Ghazali perspective that is the nature of leadership is basically innate because in fact God has chosen the child of Adam to be a prophet and leader for his people. Therefore, leadership in Islam, can not be separated from the concept of understanding the rules set by Islam based on al-Qu'ran and hadith. However, that in implementing leadership in Islam, one must have confidence that what is done and carried out is solely due to worship of Allah SWT, Characteristics of Prophetic Leadership in the Al Ghazali Perspective include: Responsibility, Hard Work, Honesty Tested and Proven, Innovative and Reformative, Have Skills and Professionals, and Bring Conducive Change.